Students' Perception Toward Podcast Media in Learning English Speaking Skills at Zainul Hasan Genggong Islamic University - Humairoh, Intan; islam, muhammad hifdzil; fatmawati, ririn (Universitas Nurul Jadid, 2024)
In the modern era of technology, there are many applications, both online and offline, that can help them learn to speak, for example, podcasts. Podcast is a platform for storing sound recordings that can be listened to anytime and anywhere. The purpose of this study is to find out how students perceive podcast media in learning English speaking skills to improve their speaking skills. The researcher used a descriptive qualitative method and involved three students. They were fourth-semester English class students in the 2023–2024 academic year. Data was collected through semi-structured interviews and observations. The researcher classified six elements based on the results of this study: technological advances in the digital era, first impressions, and effectiveness of using media podcasts, advantages of media podcasts, student motivation, and teaching podcasts in the technological era. The results show that students have a positive perception of the use of podcasts in speaking and learning. Podcasts have many contents or topics that they can listen to and learn to speak whenever they want, which makes students see it as an interesting medium. They also agree that podcasts help students speak in public, as they can improve their vocabulary and pronunciation by listening to native speakers.Keyword: students’ perception, podcast media, speaking skill